Project-Based Environmental Science Learning to Create Environmental Care Character - Siti Roudlotul Hikamah; Hariyanto Hariyanto (UIN Fatmawati Sukarno Bengkulu, 2025)
Garbage, mainly plastic, in Jember Regency needs to be appropriately managed; many are found in rivers and scattered in gardens. This research aims to realize the character of students who care about the environment; research is carried out using projects. This type of research is Research and Development (R&D) adapting the development model from Plomp through 3 stages, namely: 1) analysis); 2) design and develop prototypes; 3) evaluate. In the analysis phase, observations were made at TPSS and TPSA, and distributing environmental care character questionnaires were sent to 23 students. At the design and development prototype stage, a project is carried out to realize the character of caring for the environment through recycling waste into valuable products. At the evaluation stage, questionnaires were distributed about environmental care characters to 23 students, and product evaluation, namely writing the manuscript of the project that had been carried out. The results of TPSS and TPSA observations around the PTS campus in Jember, the average relative value was 9.47, which was in the less category. In contrast, students' environmental care character values before project implementation obtained an average score of 40.41, below expectations. The evaluation results at the design and development stages, namely recycling waste into valuable products, obtained an average of 81.67 in the category of exceeding expectations. The results of the product evaluation, namely the character value after carrying out project activities, obtained a character value of 77.04 which is in the excellent category while recycling waste into valuable products that have been written into manuscripts with an average value of 79.46 is in the excellent category. These results indicate that project-based learning is suitable for realizing the character values of students caring about the environment